2002
DOI: 10.1103/physrevb.65.235205
|View full text |Cite
|
Sign up to set email alerts
|

Bound magnetic polaron interactions in insulating doped diluted magnetic semiconductors

Abstract: The magnetic behavior of insulating doped diluted magnetic semiconductors (DMS) is characterized by the interaction of large collective spins known as bound magnetic polarons. Experimental measurements of the susceptibility of these materials have suggested that the polaron-polaron interaction is ferromagnetic, in contrast to the antiferromagnetic carrier-carrier interactions that are characteristic of nonmagnetic semiconductors. To explain this behavior, a model has been developed in which polarons interact v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
138
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(147 citation statements)
references
References 28 publications
7
138
0
1
Order By: Relevance
“…21,32,36 Again with the lowering of temperature both polaron size and total intrapolaron exchange energy increase logarithmically and probability of overlapping of BMPs and interactions between BMPs increases, which leads to the prominent long range FM ordering in the sample at low temperature. 34,37 Compared to other previously reported work on doped Gd 2 18 exhibits paramagnetic nature with maximum magnetization at 300 K around 5.7 emu/g with a maximum applied field of $ 5 T. Hazarika et al 39 reported the superparamagnetic behavior of Gd 2 O 3 nanorod at 300 K with maximum magnetization $ 6 emu/g at 6 T. Patel et al 32 reported that the paramagnetic behavior with feeble antiferromagnetic contribution in Co doped Gd 2 O 3 nanorod with maximum magnetization at 300 K was $ 0.06 emu/g with a maximum applied field of $ 2 T. But in the present system, we have investigated the magnetic properties of Ni doped Gd 2 O 3 (Gd 1.90 Ni 0.10 O 3Àd ), where room temperature ferromagnetism is observed in the low field region ($ 4000 Oe), but with maximum applied field of $ 5 T dominant paramagnetic behavior with maximum magnetization at 300 K is $ 5.8 emu/g is found. The formation of oxygen vacancy to maintain charge neutrality in GNO plays a key role for the enhancement of magnetization compared to Co and Fe doped Gd 2 O 3 .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…21,32,36 Again with the lowering of temperature both polaron size and total intrapolaron exchange energy increase logarithmically and probability of overlapping of BMPs and interactions between BMPs increases, which leads to the prominent long range FM ordering in the sample at low temperature. 34,37 Compared to other previously reported work on doped Gd 2 18 exhibits paramagnetic nature with maximum magnetization at 300 K around 5.7 emu/g with a maximum applied field of $ 5 T. Hazarika et al 39 reported the superparamagnetic behavior of Gd 2 O 3 nanorod at 300 K with maximum magnetization $ 6 emu/g at 6 T. Patel et al 32 reported that the paramagnetic behavior with feeble antiferromagnetic contribution in Co doped Gd 2 O 3 nanorod with maximum magnetization at 300 K was $ 0.06 emu/g with a maximum applied field of $ 2 T. But in the present system, we have investigated the magnetic properties of Ni doped Gd 2 O 3 (Gd 1.90 Ni 0.10 O 3Àd ), where room temperature ferromagnetism is observed in the low field region ($ 4000 Oe), but with maximum applied field of $ 5 T dominant paramagnetic behavior with maximum magnetization at 300 K is $ 5.8 emu/g is found. The formation of oxygen vacancy to maintain charge neutrality in GNO plays a key role for the enhancement of magnetization compared to Co and Fe doped Gd 2 O 3 .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The magnetic behavior of doped diluted magnetic semiconductors is characterized by the interaction between large collective spins which are known as bound magnetic polarons (BMPs). 34 According to the Hund's rule and Pauli Exclusion Principle, spin orientations of the trapped electrons and the neighbouring Ni ions should be parallel in order to achieve ferromagnetic ordering. 35 Moreover, the doping of Ni 2+ ions may enhance the number of oxygen vacancies in doped Gd 2 O 3 to maintain charge neutrality in the system.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Whether this exchange coupling is ferromagnetic or antiferromagnetic is still subject to debate. [32][33][34] A Kondo-lattice model containing the impurity orbitals and their hybridization with the conduction band was also formulated for this topic. 35 According to Arnold and Kroha, 29 the existence of preformed local moments at the impurity levels inside the semiconducting gap is essential to explain the distinct double-dome shape of the magnetization M(T), although it has become apparent from numerous experiments that oxygen deficiency alone, without doping localized moments, can be responsible for the unique double-dome feature.…”
Section: Introductionmentioning
confidence: 99%
“…11 The microstructural analysis does not show the formation of magnetic clusters such as Co-oxides and metallic Co (Supporting Information Figure S1). Moreover, CoO is an antiferromagnetic material, whose Néel temperature is 293 K. 14 …”
mentioning
confidence: 99%